Detection of C-polysaccharide in serum of patients with Streptococcus pneumoniae bacteraemia. Issue 9 (September 1995) - Gillespie, S H; Smith, M D; Dickens, A; Raynes, J G; McAdam, K P
Abstract : AIM–To investigate the fate of Streptococcus pneumoniae C-polysaccharide antigen in serum in patients with S pneumoniae bacteraemia. METHOD–In vitro dissociation experiments were performed to demonstrate that C-polysaccharide was masked by ligands in normal and acute phase serum. Serum samples from 22 patients with S pneumoniae bacteraemia were treated to dissociate immune complexes and then tested for C-polysaccharide by enzyme linked immunosorbent assay (ELISA). RESULTS–C-polysaccharide antigen was masked in normal and acute phase serum but could be released by EDTA treatment and detected by ELISA. Antigen was found in six patients ranging in concentration from 2.5 to 200 ng/ml. Patients with detectable antigen were more likely to die than those in whom antigen was not detected. CONCLUSION–This study demonstrates that C-polysaccharide antigen commonly circulates in patients with S pneumoniae bacteraemia but its presence is masked by ligands present in serum.